(3TQa GdWHs - (3Ydj Hf QVhGf Hf Ydj Hf LYaQ, CHh GdMSf,J (B453 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd ai efGaY GdWH heMGSfg (B: (3bGd Ydi Hf QVhGf (B_ (3efGaY GdWH heMGSfg cKjQI , efgG ai GdHOf hefgG ai GdfaS s
(3BNQgG (B:s
(3Hd GSJYed UfGYI GdJMdjd aCSCd Gddg Cf jYjfc hjHdZc eWdhHc s
(3ebGdI QJHgG Ydi SHYI CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B94s
GAL - (3GdLRA (B1 - (3U (B484 ; GALS - (3GdLRA (B1 - (3U (B886 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B117 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg Mcje ChZdhG Ydi HGTG (B(691(2)) s
Keywords: (3GdWHs